Investigating the Synergistic Anticancer Potential of Baicalein in HCT-116 Cells - Hala Almuwallad; Haifa Alhadi; Bassam Tomihi; Maher M Albalawi (International Journal of Medical Toxicology and Legal Medicine, 2025)
Baicalein is naturally available in the roots of Scutellaria baicalensis Georgi. It can initiate apoptosis in different types of cancer cells. However, the safety and effectiveness of baicalein on colon cancer HCT-116 cells is currently unknown. The present study takes diverse ways to examine the potential of baicalein against colon cancer cells. The findings showed that baicalein can initiate apoptosis, suppress cell growth, and reduce sirtuin 1 and survivin levels, and upregulate p21 and antioxidant genes. While exploring the most synergistic anticancer combinations with baicalein, the results showed that baicalein in the company of 100 nM quinacrine can prevent the HCT-116 cell count most effectively. Baicalein in combination with 100 μM quinacrine and 5 μM doxorubicin showed a significant increase in lysosomal membrane permeabilization. In summary, the findings indicate that baicalein could inhibit the growth of human colon cancer HCT-116 cells by initiating the expression levels of antioxidant and apoptotic genes, and in synergy with quinacrine and doxorubicin can show an additional effect on HCT-116 cells.